The Age of Turbulence - Credit Derivatives Style - Hans Byström (Lund University, School of Economics and Management, Department of Economics, 2010)
This paper focuses on the many extreme credit default swap spread movements observed during the recent credit crisis and on how the tails of the spread (and price) change distribution significantly differ from those of the normal distribution even for diversified credit derivatives portfolios. Particular focus is put on the sudden shift in the behavior of the credit default swap market in the summer of 2007. During the first month of the crisis, July 2007, we find the extreme turbulence in the credit derivatives market to be comparable only to the turmoil in the equity market in October 1987 and in October 2008. As a result of this extreme behavior and the dramatic regime shift observed in 2007, credit derivatives portfolio Value at Risk estimates based on extreme value theory are found to be much more accurate than those based on normal or historical distributions, both during the crisis and in the comparably tranquil times leading up to the crisis.
Keywords: C16; G01; G10; G33; 330; value at risk; VaR; extreme value theory; credit default swap index; credit crisis; credit derivative